On the Alternation between Complex Prepositions and Adverbial Prepositions in Esperanto, such as en la mezo de vs. meze de / en la kadro de vs. kadre de - Gledhill, Christopher (Investigationes Linguisticae, 2023)
The grammar of Esperanto allows a derived adverbial to replace the initial element in any complex prepositional phrase, thus creating a range of equivalent structures such as en la mezo de / meze de ‘in the middle of’, en la kadro de / kadre de ‘in the framework of’ etc. This ‘adverbial alternation’ raises a number of questions. Are Adv Ps interchangeable with their Complex P counterparts? Do they occur with the same frequency? Does lexicalisation operate in the same way in Esperanto as it does in other languages? Here I examine a sample of alternating structures in a corpus of standard written Esperanto (Tekstaro >10 million tokens). While many pairs seem to be interchangeable, others appear to be developing contrastive use. The use of idioms and other marked units of phraseology is often seen as evidence that Esperanto has become an autonomous language. Here I point to evidence of less marked, more routine patterns of discourse which are unique to this speech community.